Fuzzy analytic hierarchy process (FAHP) for multi-criteria selection of microalgae harvesting and drying processes - Tan, Jully (Animo Repository, 2016)
© 2016, Springer-Verlag Berlin Heidelberg. Microalgae are considered to be a promising source of biomass compared with first and second generation feedstocks. However, the high energy requirement for harvesting and drying of the algal biomass poses challenge to commercialization due to implications on both carbon footprint (CF) and cost. In this work, we propose a systematic methodology for the multi-criteria evaluation of alternatives for the harvesting and drying processes. A fuzzy analytic hierarchy process (FAHP) approach is used, where the pairwise comparison of the multiple criteria and alternatives were done to prioritize the best harvesting and drying method within the fuzzy bounds of the value judgment that satisfies the consistency index. FAHP also allows the degree of confidence of the expert to be quantified. A case study of four alternatives each for the harvesting and drying process is used to demonstrate the process. Technology capability, cost and environmental impacts (comprised CF, land footprint and water footprint) are identified as the selection criteria for harvesting and drying process, respectively. Results show that flotation is the best alternative for harvesting process, while sun drying is the best among the drying alternatives. Sensitivity analysis is used to give insights on the robustness of the decision model and enables the understanding of critical criteria that would significantly influence the ranking of the alternatives. The proposed FAHP approach therefore can effectively deal with the uncertainty of judgment in the decision-making process in the evaluation of microalgae harvesting and drying processes.